Influence of post-transplant immunosuppressive therapy on gastrointestinal transit using biomagnetic method: a pilot study - Teixeira, Maria do Carmo B.; Americo, Madileine F.; Oliveira, Ricardo B.; Miranda, Jose Ricardo A. [UNESP]; Romeiro, Fernando G. [UNESP]; Cora, Luciana A. (Springer, 2015)
Background Immunosuppressive therapy after kidney transplant is necessary to prevent allograft rejection and it is the cause of several gastrointestinal (GI) disorders that have been scantily studied.Objectives This study was aimed at investigating the influence of triple immunosuppressive therapy on GI transit in renal transplant patients by employing a biomagnetic technique.Methods Twenty-one renal transplant patients underwent triple therapy, which included either tacrolimus (TAC) or cyclosporin A (CsA) associated with prednisone and azathioprine. They were all evaluated, and fifteen other healthy individuals formed the control group. After a standardized meal, GI transit of magnetic markers was assessed using Alternating Current Biosusceptometry (ACB).Results Patients taking TAC had significantly accelerated gastric emptying and colonic arrival (p <= 0.001) when compared with those taking CsA and those in the control group. However, no differences were observed in small bowel transit among the groups studied. Overall, the intersubject coefficients of variation for gastrointestinal transit parameters were higher for the TAC group and similar for the CsA and control groups.Conclusion This study demonstrated that ACB is a suitable methodology when evaluating the influence of different immunosuppressive therapies on gastrointestinal transit after renal transplantation. Pronounced inter-individual variation was found in patients treated with tacrolimus, thus showing the prokinetic effect of this drug on GI motility. Studies of motility patterns in this population could be useful as complementary information toward determining the mechanisms and the relationship between motility and therapeutic doses.
Keywords: Azathioprine; Cyclosporin A; Gastrointestinal motility; Prednisone; Renal transplant; Tacrolimus